PEMBELIAN PANGAN MELALUI PEMANFAATAN SISTEM ONLINE PADA MASYARAKAT URBAN DI MASA PANDEMI COVID-19 - Vi'in Ayu Pertiwi (University of Jember, 2021)
The Covid-19 pandemic has had a major impact on the people's economy, even in matters of meeting daily food needs. Urban communities are required to limit their activities to leave their homes, keep their distance from other people, and avoid crowds during the pandemic period as recommended by government health protocols. Food is one of the basic needs that must be fulfilled every day by the community. The online food purchasing system is an alternative solution to this problem. Then an analysis of the factors that influence urban communities to purchase food online during the pandemic is carried out. The research was conducted in Malang City, East Java Province in June-September 2020. The research approach used was quantitative with a survey method using an online questionnaire. The samples were determined using a convenience sampling technique with 100 respondents who purchased food online during the pandemic. The results showed that psychology and perception variables had a significant and positive effect, while social variables had a significant and negative effect on online food purchases during the Covid-19 pandemic.